Proceedings the Seventh IEEE European Test Workshop
DOI: 10.1109/etw.2002.1029634
|View full text |Cite
|
Sign up to set email alerts
|

Modeling gate oxide short defects in CMOS minimum transistors

Abstract: In this paper a new model is proposed for Gate Oxide Short defects based on a non-split MOS transistor. Because the MOS is not split, this model allows to simulate minimum transistors in realistic digital circuits. The construction of the model is presented in details using a comprehensive and didactic approach. It is demonstrated that the electrical behavior of the proposed model matches in a satisfactory way the defective transistor behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The state-of-the-art in OBT testing [8][9][10]14] uses 10 Ω resistors to represent short circuit faults and 10 MΩ resistors to represent open circuit faults. As open and short circuits on-chip may assume a wide variety of impedance values [18], it would be prudent to analyse the effect of substituted impedance value variation on the OBT technique.…”
Section: Evaluation Of Short Circuit and Open Circuit Impedance Valuesmentioning
confidence: 99%
“…The state-of-the-art in OBT testing [8][9][10]14] uses 10 Ω resistors to represent short circuit faults and 10 MΩ resistors to represent open circuit faults. As open and short circuits on-chip may assume a wide variety of impedance values [18], it would be prudent to analyse the effect of substituted impedance value variation on the OBT technique.…”
Section: Evaluation Of Short Circuit and Open Circuit Impedance Valuesmentioning
confidence: 99%
“…Dependent current source model and diode-resistance model were developed by Rodriguez [2][3]. Renovell proposed bi-dimensional model, linear nonsplit MOS model, and nonlinear nonsplit model [4][5][6]. In addition, Yassine presented a method that differentiated gate oxide failures from silicide bridging between gate and source/drain [7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to develop accurate defect models that can be used in obtaining reliable fault models and practical test patterns. There are two types of GOS model for MOSFETs, split and non-split [63]. In the split model, a bidimensional array of transistors are used as an electrical model of a defect-free transistor, Figure 3.2 (a).…”
Section: Gos Modeling In Mosfetmentioning
confidence: 99%
“…The non-split models are categorized in two groups, linear and non-linear [63]. In [32], authors have proposed the nonlinear non-split model shown in Figure 3.4 (a).…”
Section: Gos Modeling In Mosfetmentioning
confidence: 99%